Prognostic factors for progression in patients with Philadelphia chromosome‐positive acute lymphoblastic leukemia in complete molecular response within 3 months of therapy with tyrosine kinase inhibitors. Issue 15 (1st April 2021) - Sasaki, Koji; Kantarjian, Hagop M.; Short, Nicholas J.; Samra, Bachar; Khoury, Joseph D.; Kanagal Shamanna, Rashmi; Konopleva, Marina; Jain, Nitin; DiNardo, Courtney D.; Khouri, Rita; Garcia‐Manero, Guillermo; Kadia, Tapan M.; et al.
Abstract : BACKGROUND: The achievement of a 3‐month complete molecular response (CMR) is a major prognostic factor for survival in patients with Philadelphia chromosome (Ph)‐positive acute lymphoblastic leukemia (ALL). However, 25% of patients relapse during therapy with tyrosine kinase inhibitors (TKIs). METHODS: The authors reviewed 204 patients with Ph‐positive ALL who were treated between January 2001 and December 2018 using the combination of hyper‐CVAD (hyperfractionated cyclophosphamide, vincristine, doxorubicin, and dexamethasone) plus a TKI (imatinib, 44 patients [22%]; dasatinib, 88 patients [43%]; or ponatinib, 72 patients [35%]). Progression‐free survival (PFS) was defined as the time from the start date of therapy to the date of relapse, death, or last follow‐up. Overall survival (OS) was defined as the time from the start date of therapy to the date of death or last follow‐up. RESULTS: Overall, a 3‐month CMR was observed in 57% of patients, including 32% of those who received imatinib, 52% of those who received dasatinib, and 74% of those who received ponatinib. The median follow‐up was 74 months (imatinib, 180 months; dasatinib, 106 months; ponatinib, 43 months). Among 84 patients in 3‐month CMR, 17 (20%) proceeded to undergo allogeneic stem cell transplantation (ASCT). The 5‐year PFS and OS rates were 68% and 72%, respectively. By multivariate analysis, ponatinib therapy was the only significant favorable independent factor predicting for progression ( P = .028; hazard ratio, 0.388; 95% CI, 0.166‐0.904) and death ( P = .042; hazard ratio, 0.379; 95% CI, 0.149‐0.966). ASCT was not a prognostic factor for PFS and OS by univariate analysis. CONCLUSIONS: In patients with Ph‐positive ALL, ponatinib is superior to other types of TKIs in inducing and maintaining a CMR, thus preventing disease progression. ASCT does not improve outcome once a 3‐month CMR is achieved. Abstract : Ponatinib is superior to other types of tyrosine kinase inhibitors in inducing and maintaining a complete molecular response, thus preventing progression in patients with Philadelphia chromosome‐positive acute lymphoblastic leukemia. Allogeneic stem cell transplantation does not improve outcomes once a 3‐month complete molecular response is achieved.